Pengaruh Keahlian Komite Audit Terhadap Manajemen Laba Pada Bisnis Manufaktur - Auliana, Rini Adriani (Income : Digital Business Journal, 2025)
This research aims to examine the influence of audit committee expertise in limiting earnings management to avoid a decrease in profits. The population of this research is manufacturing companies listed on the Indonesia Stock Exchange during 2017-2020. The sampling technique used purposive sampling and obtained a sample size of 102 companies with 408 observations. The analysis technique uses multiple linear regression analysis. The research results show that accrual and real earnings management is used by managers to avoid a decrease in profits. Earnings management practices can be limited by the expertise of the audit committee. Real earnings management can be limited by the expertise of the audit committee. This research provides empirical evidence of positive accounting theory as well as empirical evidence of agency theory, namely that the thing that can limit real earnings management is the expertise of the audit committee. Investors can be more careful in determining investment decisions. Investors must pay attention to the expertise of the company's audit committee as stated in the company's annual report